Search and detection of remote sensing objects - A. I. Mitsiukhin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Spectral method for image search and discovery of the object with the specified geometric characteristics is analyzed. In comparison with the famous search algorithms described algorithm allows to reduce time of search, computational complexity of digital imaging, simplifies the decoding images. The method can be applied in solving problems such as segmentation, image combining, recognition, determining the distance between objects and phenomena, determining the dynamic characteristics of objects.